Concepções do professor de arte sobre aspectos de sua formação para atuar com alunos surdos - Batista, Flóida Moura Rocha Carlesso [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Professionals training should consider that the human being, inserted in educational processes, is firstly a person, the subject of his own construction. Inclusive education, which motivated this research, although it is a complex task, cannot be conceived as an obstacle, but as one of many challenges in the world of Education. Under this view, this study aimed to investigate the educational and continuing training of Art teachers to work in the education of deaf students. Therefore, eight teachers who teach the Art matter in state public schools and have deaf students in their classrooms were invited. These teachers were interviewed, through a semi-structured script. Next, the interviews were transcribed and were analyzed through its content, establishing themes that could answer the purpose of this study. The results were discussed based on the theoretical foundations researched on the subject. This analysis resulted in three themes, namely: initial and continuing training as a support for the practice in inclusive education; support for working in the classroom; and the art matter and the participation of deaf students. The results showed that from the perspective of inclusion of the deaf in school, it is necessary the teacher to think carefully to decide what resources and services can and should be used to support the teaching processes. The simplicity of the services offered for inclusion can be noticed in daily intercourse within the school, with the conceptual and operational issues, as simplicity helps teachers better understand their practices and thus improve them. The analysis of categories also indicates that if it is not yet possible to find the inclusive school everywhere, in all social groups and in all parts of the country, it is necessary to start building ways so it can reach all of them. In this regard, thinking what a learning environment for the formalization of learning is a great way to start. The first category...

A formação de profissionais deve considerar que o ser humano, inserido nos processos educacionais é primordialmente pessoa, sujeito da elaboração do próprio conhecimento. A educação inclusiva, que moveu a presente pesquisa, muito embora seja uma tarefa complexa, não pode ser concebida como um desafio, mas como um dentre tantos desafios no mundo da Educação. Sob essa ótica, esta pesquisa teve como objetivo investigar aspectos das formações inicial e continuada do professor de arte para atuar na educação do aluno surdo. Para tanto, foram convidadas oito professoras que atuavam com a disciplina de Arte no ensino público estadual e que possuíam em suas salas de aula, alunos surdos. Essas professoras foram entrevistadas, com o apoio de um roteiro semiestruturado. Em seguida, essas entrevistas foram transcritas na íntegra e analisadas por meio de seu conteúdo, estabelecendo-se categorias temáticas que pudessem responder ao objetivo desse estudo. Essa análise culminou em três categorias temáticas, a saber: formação inicial e continuada como suporte para a prática na educação inclusiva; apoios para trabalhar em sala de aula; e disciplina de arte e a participação dos alunos surdos. Os resultados indicaram que, sob a ótica da inclusão do surdo na escola, é preciso que o professor avalie para decidir, criteriosamente, que recursos e serviços ele pode e deve utilizar para respaldar os processos de ensino. A primeira categoria mostrou que as formações inicial e continuada do professor, amparadas pelo foco da inclusão, precisam ser acrescidas de estudos e pesquisas que encaminhem o professor a simplificar o trato com o aluno surdo, oportunizando-o aos novos conhecimentos; a segunda categoria, a respeito dos apoios para trabalhar com o aluno surdo, indica que, embora as professoras entrevistadas apontem que que têm domínio dos processos em sala de aula, muitas situações dessa relação ensino-aprendizagem ainda as...
Keywords: Professores - Formação; Professores de arte; Educação inclusiva; Surdos - Educação; Deficientes auditivos; Inclusive education